2015
DOI: 10.3389/fphys.2015.00160
|View full text |Cite
|
Sign up to set email alerts
|

The lowering effect of Gum Arabic on hyperlipidemia in Sudanese patients

Abstract: Hyperlipidemia especially low density lipoprotein cholesterol (LDL-C) is a major risk factor for developing ischemic heart disease. Soluble dietary fiber has lipid lowering characteristics. Gum Arabic (GA) is 95% soluble fiber calculated on dry bases. The beneficial effect of GA on lipid profile needs further verification. A case–control study was conducted at Omdurman Hospital, Sudan to assess the effect of G A on serum lipids in patients with hyperlipidemia. Cases received a 20 mg tablet of atorvastatin /day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 27 publications
4
15
0
1
Order By: Relevance
“…GA did not increase HDL level, which would be favorable for SCD patients. Our results are consistent with previous study conducted among Sudanese population; GA reduced LDL with no effect on HDL [30]. And other contradictory outcomes revealed the augmenting effect of GA on HDL among diabetic patients [31].…”
Section: Discussionsupporting
confidence: 92%
“…GA did not increase HDL level, which would be favorable for SCD patients. Our results are consistent with previous study conducted among Sudanese population; GA reduced LDL with no effect on HDL [30]. And other contradictory outcomes revealed the augmenting effect of GA on HDL among diabetic patients [31].…”
Section: Discussionsupporting
confidence: 92%
“…We also have observed that added AF caused foaming of the final product. This may be due to the fact that AF contains about 95% of soluble fibres (Mohamed et al , ). In each of the studied cases, the shear thinning was observed from 0 to 5 s. At intermediate shear rates from 5 to 15 s viscosity decreased and then became almost constant.…”
Section: Resultsmentioning
confidence: 99%
“…It is known from our previous in vitro studies that L. plantarum MBTU-HK1 has the ability to assimilate cholesterol from growth media (due to the production of the BSH enzyme), and thus the reduced level of cholesterol in the probiotic and synbiotic groups can be attributed to the bile salt hydrolase activity of the test strain. The results obtained in the in vitro study have thus been proven in the in vivo experiments in [25][26][27][28]. In all the treatment groups triglycerides were reduced and the synbiotic group possessed the lowest level of triglycerides, which is supported by the results of [29], which demonstrated that L. acidophilus and B. bifidum can significantly decrease the serum levels of LDL and triglycerides.…”
Section: Discussionmentioning
confidence: 55%